Migrating Applications to the Cloud - Swoyer, Steve; Swoyer, Steve (O'Reilly Media, Inc., 2021)
Cloud environments provide many well-known advantages, including flexibility, scalability, reliability, and high availability. But a lot of businesses still find themselves running some or all of their application suites and databases on-premises. If your enterprise is considering a migration to the cloud, it's critical you evaluate ways to make the move without introducing new risks or complexities. This report provides a concise yet comprehensive overview of migrating applications to the cloud. IT decision makers will learn how to create a migration plan to fit their company's needs, using best practices, tools, and available services. Analyst Stephen Swoyer reviews the benefits of migrating to the cloud, from cost-effectiveness to the acceleration of new technology adoption. You'll understand the challenges involved in migration and learn how to create a strategy to reduce risks and increase the likelihood of success. This report explores: The benefits of cloud migration, including cost-effectiveness, security, and the quick adoption of new technologies How to craft a migration strategy to reduce risks when preparing to move any workload, data, or application to the cloud.